A Coupled Fixed Point Theorem in Fuzzy Metric Space Satisfying ϕ-Contractive Condition. (3rd October 2013) - Pant, B. D.; Chauhan, Sunny; Vujaković, Jelena; Khan, Muhammad Alamgir; Vetro, Calogero
Abstract : The intent of this paper is to prove a coupled fixed point theorem for two pairs of compatible and subsequentially continuous (alternately subcompatible and reciprocally continuous) mappings, satisfying ϕ -contractive conditions in a fuzzy metric space. We also furnish some illustrative examples to support our results.